Hot dog, cold dog. - Children's Press (New York, N.Y.) (New York, NY : Children's Press, an imprint of Scholastic, 2017)
Offers photograph illustrations that compare dogs that exemplify such opposites as hot and cold, big and small, curly and straight.
Cover title.
Keywords: Dogs -- Juvenile literature; English language -- Synonyms and antonyms -- Juvenile literature; Board books; Dogs; English language -- Synonyms and antonyms; Board books; Dogs; Opposites; English language -- Synonyms and antonyms; Board books for children